Patient Doses in Simple Radiographic Examinations in Trang, Phatthalung and Satun Provinces in the Transition from X-ray Film to Computed Radiography - Buncharat, Siriwan; Hamuttiti, Pattarapong (Journal of Health Science of Thailand, 2017)
High radiation dose can induce radiation hazard to patients, the dose justification and optimization are essential. Currently, many hospitals have changed radiographic services from X-ray film to the computed radiography systems. The objective of this study was to assess doses of radiation among patients receiving simple radiographic examinations. It was conducted during January - June 2015 in the regional, general and community hospitals under the supervision of the Regional Medical Sciences Center 12/1, Trang, which include Trang, Phatthalung and Satun provinces. There were 24 hospitals participating the study. Of all the 24 general X-ray units, 15 were computed radiography, 1 was digital radiography, and 8 were using X-ray film. The International Atomic Energy Agency (IAEA) computation method was utilized; and compared the doses with the diagnostic reference levels studied by Department of Medical Sciences in 2011 and IAEA. The doses were calculated from exposure technique used for 60±15 kg size patients of seven most common radiographic examinations: chest PA, lumbar-sacral spine PA and lateral, pelvis AP, abdomen AP, skull AP/PA and lateral. There were altogether 1,917 patients receiving the services during the study period. It was found that the mean/third quartile dose for each of the 7 examinations was 0.3/0.3, 4.1/6.1, 10.9/14.6, 3.4/5.4, 4.6/4.7, 2.7/4.0, 2.1/3.0 mGy, respectively; and the third quartile values of this study were higher than the reference dose of Department of Medical Sciences in 2011 and IAEA. Hospitals using computed radiography systems used higher dose than the Xray film systems. To reduce radiological exposure to patients, the study results were sent to the radiographers to review their practice in order to adjust patient dose to be as low as possible.